Pengaruh Senam Jantung Sehat terhadap Tekanan Darah Penderita Hipertensi di Wilayah Kerja Puskesmas Lepo-Lepo - Amiruddin Eso; Dwi Pascawitasari; I Putu Sudayasa (Halu Oleo University, 2018)
ABSTRACTHypertension is the increase in systolic and diastolic blood pressure that occurs persistently. Healthy heart gymnastic is one of the non pharmacologic therapies for hypertensive patients. Healthy heart gymnastic can increase activity of parasympathetic nerve and decrease activity of sympathetic nerve, so that could lead decrease of blood pressure. The aim of this research was to find out the effect of healthy heart gymnastic towards blood pressure before and after exercise in hypertensive patients. Research design was quasi experimental with pre test and post test control group design. The Samples were 20 hypertensive patients aged 18 to 65 years, determined by using purposive sampling techniques. Samples were divided into two groups, i.e control group (n=10) consisted of 3 males and 7 females and intervention group (n=10) consisted of 10 females. Healthy heart gymnastic Intervention implemented during four weeks with modrate intensity (60% MHR) and fifth times in a week. The research was held in Health Centers Lepo-Lepo, Kendari, Southeast Sulawesi. Measurement of blood pressure by indirect method and measurements of pulse pressureby pulse meter. Data were analyzing by paired t test for systolic blood pressure in intervention group and Wilcoxon test for diastolic blood pressure in intervention group. Data have considered if p value < 0,05. The results have shown there were significant differences in systolic blood pressure (p = 0,000) and diastolic blood pressure (p = 0,004) before and after healthy heart gymnastic in intervention group. Conclusion of this research is healthy heart gymnastic can decrease blood pressure in hypertensive patients, so that usable as one of alternative treatment in hypertensive patients.Key Words: healthy heart gymnastic, hypertension, decrease of blood pressure, health centers lepo-lepo